Permainan sensori motorik untuk meningkatkan konsentrasi pada anak dengan ADHD - Nur Rahmatul Azkiya (Universitas Muhammadiyah Malang, 2021)
The subject is a child with ADHD disorder with problems of lack of concentration and attention that is easily distracted. This affects performance in school and schoolwork that is not completed. Sensory Motor Play was done to improve the concentration of subjects so that their performance in school becomes better. This intervention uses a wide variety of games so that the subject was not easily bored and involves physical activity. The results of the intervention found that the concentration of the subject increased which was characterized by several completed tasks, showed the behavior of being able to wait in line and be able to control their voice.